2020
DOI: 10.3892/ijo.2020.5002
|View full text |Cite
|
Sign up to set email alerts
|

HECTD1 regulates the expression of SNAIL: Implications for epithelial‑mesenchymal transition

Abstract: As a transcription factor, SNAIL plays a crucial role in embryonic development and cancer progression by mediating epithelial-mesenchymal transition (EMT); however, post-translational modifications, such as ubiquitination, which control the degradation of SNAIL have been observed to affect its functional role in EMT. In a previous study by the authors, it was demonstrated that the HECT domain E3 ubiquitin ligase 1 (HECTD1) regulated the dynamic nature of adhesive structures. In the present study, HECTD1 was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…There are three types of EMT (type 1, 2, and 3) which exert different functions. Type 1 occurs in the embryonic stage and is related to the growth and development of the embryo [ 16 ]. Type 2 participates in wound healing, tissue regeneration and organ fibrosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are three types of EMT (type 1, 2, and 3) which exert different functions. Type 1 occurs in the embryonic stage and is related to the growth and development of the embryo [ 16 ]. Type 2 participates in wound healing, tissue regeneration and organ fibrosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of EMT is essential during development, but it can also be triggered in various cancers through influencing cell-cell adhesion and metastasis [ 58 ]. HECTD1 contains eight nuclear localization sequences (NLS) and four nuclear export signals (NES), giving rise to its presence within the nucleus despite typical cytoplasmic localization; this localization is specifically mediated through exportin 1 (XPO1) [ 59 ]. With this ability to translocate from the cytosol to the nucleus, HECTD1 is able to regulate zinc finger protein SNAIL1 (SNAIL) expression levels.…”
Section: Ankyrin Repeats and The Usp—working Together To Regulate mentioning
confidence: 99%
“…Based on the downregulation of HECTD1 mRNA in tumor tissues (Fig. 1) and the previous reports showing that HECTD1 suppressed EMT 10,11 , we investigated the association between HECTD1 mRNA expression and tumor aggressiveness in the NCU cohort. HECTD1 mRNA expression was signi cantly lower in larger tumors (P=0.009) and higher-grade tumors (grade 3 vs. grade 1, P<0.001; grade 3 vs. grade 2, P<0.001; grade 2 vs. grade 1, P=0.042) (Fig.…”
Section: Hectd1 Mrna Level Was Negatively Associated With Aggressive Tumor Characteristicsmentioning
confidence: 99%
“…HECTD1 was previously shown to play crucial roles in the negative regulation of cell [7][8][9][10] migration. A recent report demonstrated that HECTD1 negatively regulates epithelial-mesenchymal transition (EMT), resulting in decreased invasion and metastasis in breast cancer 11 .…”
Section: Introductionmentioning
confidence: 99%